Rheumatoid arthritis and thyroid dysfunction: A cross-sectional study and a review of the literature. Issue 5 (October 2018) - Mahagna, Hussein; Caplan, Alyssa; Watad, Abdulla; Bragazzi, Nicola Luigi; Sharif, Kassem; Tiosano, Shmuel; Mahroum, Naim; Hendel, Hen; Shoenfeld, Yehuda; Comaneshter, Doron; Cohen, Arnon D.; Amital, Howard
Abstract: Thyroid dysfunction appears to show increased prevalence in many autoimmune diseases; however, this comorbidity has not been properly investigated in patients with RA. This issue was addressed in this cross-sectional study. Using the database of the Clalit Health Services (CHS) in Israel, RA patients were paired with age- and sex-matched controls to compare the prevalence of hypothyroidism and hyperthyroidism. Chi-squared and t-tests were used for univariate analysis and a logistic regression model was used for multivariate analysis. The study included 11, 782 patients with RA and 57, 973 controls. The rate of thyroid dysfunction diseases in RA patients was increased compared with the prevalence in controls (16.0% and 11.7%, p < 0.001, for hypothyroidism; and 2.33% and 1.81%, p < 0.001 in hyperthyroidism, respectively). In a multivariate analysis, RA was associated with hypothyroidism (OR = 1.42, 95% CI 1.34–1.50) and hyperthyroidism (OR = 1.26, 95% CI 1.10–1.45). RA is associated with thyroid dysfunction. Therefore, physicians treating patients with RA should be aware of the possibility of comorbid thyroid dysfunction and treat accordingly.